INDONESIAN EDUCATION LANDSCAPE IN MALAYSIA: A PORTRAIT OF ONLINE LEARNING INDONESIAN SCHOOL OF KOTA KINABALU - Hermawan, Dadang; Aswan, Aswan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2025)
The Indonesian School of Kota Kinabalu (SIKK) is an Indonesian school located in Sabah, Malaysia. SIKK is the parent school that oversees hundreds of schools for Indonesian children in Sabah—Sarawak. Given SIKK's extensive reach, this research aims to explore how online learning has been implemented during the Covid-19 pandemic. The research method used is qualitative with a case study approach. Researchers found that SIKK implemented online learning due to the Malaysian government's prohibition on physical contact. Researchers also identified obstacles faced by students during online learning, such as difficulty accessing the internet, lack of electronic devices, and so on. Media used to support online learning include Zoom, Google Meet, and others. The conclusion that can be drawn is that SIKK has carefully designed and implemented online learning, considering various factors such as student needs, technological infrastructure, and effective teaching methods. This reflects their commitment to providing effective online education and providing an optimal learning experience for all parties involved.